Light-Induced Fluorescence Changes in Chlorella, and the Primary Photoreactions for the Production of Oxygen - Mauzerall, David (1972)
The light-induced increases of the effective fluorescence yield in Chlorella are too slow to be primary processes in photosynthesis. The fast transient state (risetime 25 nsec, limited to the first flash) is attributed to a priming reaction for the photosystem that makes oxygen. The slower cyclical process (risetime 3 μsec, decay time 200 μsec and 2 msec) is attributed to the dark reactions that make oxygen after photoexcitation of this system. The slower cyclical process is also distinguished by a narrower emission spectrum that peaks at a shorter wavelength than the dark adapted or fast transient state. A minimum of six different fluorescent states are required to explain the data. In addition to the usual assumption about changing quantum yield of fluorescence in these processes, the data suggest that changes in cross section of optical absorption must also be considered. The slowest relaxation times observed (0.2-2 msec) are well correlated with the slow steps detected in evolution of oxygen.